Radar Absorbing Materials Double Layer From Laterite Iron Rocks And Actived Carbon Of Cassava Peel In X-Band Frequency Range - Linda Silvia; Bayu Aslama; Ega Novialent; M. Zainuri (UNEJ e-Proceeding, 2016)
In recent years, laterite iron sand-actived carbon composites based on natural ingredient were successfully introduced as microwave absorbers material. In this research work, laterite iron sand-active carbon composites has been made from laterite iron rock, Tanah Laut, South Kalimantan to be laterit iron sand and active carbon will be achieve by activation method with KOH from cassava peel. This laterite iron sand-active carbon composites coating is applied to steel grade A type AH36. Microwave absorbing properties were investigated by measuring reflection loss in the 8.2-12.4 GHz microwave frequency range using network analyser. The results of microwave absorbing properties studies showed that the reflection loss of laterite iron sand-actived carbon composites is higher than uncoated steel samples.